ANALISIS PENERAPAN WEBSITE KECAMATAN GAJAHMUNGKUR DIUKUR DARI 3 ELEMEN SUKSES (SUPPORT, CAPACITY, VALUE) DI KECAMATAN GAJAHMUNGKUR KOTA SEMARANG - Nerissa Arviana Putri; Nina Widowati; Maesaroh Maesaroh (Jurusan Administrasi Publik, Fakultas Ilmu Sosial dan Ilmu Politik, Universitas Diponegoro, 2022)
The purpose of this research is to find out how the application of the website Kecamatan Gajahmungkur is measured from the 3 Elements of Success (Support, Capacity, Value) in Kecamatan Gajahmungkur, Semarang City. This study uses a qualitative-descriptive research method. The informants involved in this study were the Kepala Seksi Pelayanan Manajemen Data Diskominfo Kota Semarang, Camat Kecamatan Gajahmungkur, several people who live in the Kecamatan Gajahmungkur, Kasi Pelayanan Publik, and IT personnel in the Kecamatan Gajahmungkur. The results of this study indicate that the success implementation of the website Kecamatan Gajahmungkur made by the Diskominfo in Semarang City when viewed from the support, capacity, and value elements, is supported by several regulations that have been made to regulate the application of the website Kecamatan in Semarang City. The implementation of the website Kecamatan Gajahmungkur has also gone quite well because there are already IT personnel who handle the website Kecamatan Gajahmungkur directly. With the website Kecamatan Gajahmungkur, information can be accessed anywhere 24 hours a day, 7 days a week but when viewed from information regarding public service requirements, all kinds of activities and matters regarding Kecamatan Gajahmungkur and activities that have been carried out by the Pemerintah Kota Semarang through the website Kecamatan Gajahmungkur, in the future the Kecamatan Gajahmungkur will improve and complete the information provided on this website Kecamatan Gajahmungkur. It is recommended that the Diskominfo in Semarang City can carry out a review of the implementation of the website kecamatan not only that the implementation of socialization is also important so that people are more familiar with the website Kecamatan Gajahmungkur.